China’s foreign direct investment: driving green growth or seeking pollution havens? Based on the perspective of green total factor productivity - Pan, Zijian; Hu, Yufeng; Xu, Rongrong (Frontiers in Environmental Science, 2024)
China has significantly increased its foreign direct investment (FDI). Although these investments help to boost global development, their impacts on the environment are still controversial and deserve careful investigation. This paper uses the super-efficiency SBM model to measure the green total factor productivity (GTFP) of 123 host countries of China’s FDI. On this basis, we adopt the two-step system GMM and dynamic panel threshold effect model to analyze the impact of China’s FDI on the GTFP of host countries. The research results show that: 1) The impact of China’s FDI on the GTFP of host countries is mainly through green technology efficiency. Its impact is inhibitory, followed by a promotional one, with the latter being significantly larger than the former. 2) There is no evidence of the “pollution haven effect” associated with China’s FDI. In fact, for countries with lower environmental regulations, China’s FDI promotes the growth of GTFP more effectively. 3) The innovation level of host countries moderates the relationship between China’s FDI and GTFP growth. For host countries with stronger innovation level, their GTFP growth can be enhanced to a greater extent by China’s FDI.